First insights into the transcriptome and development of new genomic tools of a widespread circum‐Mediterranean tree species, Pinus halepensis Mill. (4th March 2014) - Pinosio, S.; González‐Martínez, S. C.; Bagnoli, F.; Cattonaro, F.; Grivet, D.; Marroni, F.; Lorenzo, Z.; Pausas, J. G.; Verdú, M.; Vendramin, G. G.
Abstract Aleppo pine (Pinus halepensis Mill.) is a relevant conifer species for studying adaptive responses to drought and fire regimes in the Mediterranean region. In this study, we performed Illumina next‐generation sequencing of two phenotypically divergent Aleppo pine accessions with the aims of (i) characterizing the transcriptome through Illumina RNA‐Seq on trees phenotypically divergent for adaptive traits linked to fire adaptation and drought, (ii) performing a functional annotation of the assembled transcriptome, (iii) identifying genes with accelerated evolutionary rates, (iv) studying the expression levels of the annotated genes and (v) developing gene‐based markers for population genomic and association genetic studies. The assembled transcriptome consisted of 48 629 contigs and covered about 54.6 Mbp. The comparison of Aleppo pine transcripts to Picea sitchensis protein‐coding sequences resulted in the detection of 34 014 SNPs across species, with a Ka/Ks average value of 0.216, suggesting that the majority of the assembled genes are under negative selection. Several genes were differentially expressed across the two pine accessions with contrasted phenotypes, including a glutathione‐s‐transferase, a cellulose synthase and a cobra‐like protein. A large number of new markers (3334 amplifiable SSRs and 28 236 SNPs) have been identified which should facilitate future population genomics and association genetics in this species. A 384‐SNP Oligo Pool Assay for genotyping with the Illumina VeraCode technology has been designed which showed an high overall SNP conversion rate (76.6%). Our results showed that Illumina next‐generation sequencing is a valuable technology to obtain an extensive overview on whole transcriptomes of nonmodel species with large genomes.